Two‐stage anaerobic digestion for reduced hydrogen sulphide production. Issue 4 (8th April 2015) - Moestedt, Jan; Nordell, Erik; Hallin, Sara; Schnürer, Anna
Abstract: BACKGROUND: This study evaluated a two‐stage process as an alternative to single‐stage anaerobic degradation, with the aim of separating sulphidogenesis and methanogenesis while treating a mixture of organic fraction municipal solid waste (OFMSW) and thin stillage. For full‐scale applications, no pH regulation was applied. The hydrolytic/acidogenic stage was evaluated with a hydraulic retention time (HRT) between 3 and 15 days, with and without recirculation of methanogenic stage reactor material. RESULTS: Homoacetogenesis dominated in the hydrolytic/acidogenic stage. However, sulphate reduction was unsuccessful. Using a two‐stage approach with OFMSW at a HRT of 10 days in the first stage and 28 days in the second stage resulted in a 12% increase in specific methane production and a 6% increase in methane content. The two‐stage process with thin stillage was less effective, probably because of decreasing pH (<4) in the first stage. CONCLUSION: Two‐stage operation resulted in a pH too low ( 4) for successful sulphate reduction in the first stage. However the resulting pH and applied organic loading rate caused homoacetogenesis to dominate, producing acetate as a favourable energy carrier between the stages. © 2015 Society of Chemical Industry